Analisis Kinerja Keuangan Pemerintah Kota Bandung Ditinjau Dari Rasio Efektivitas, Rasio Efisiensi dan Rasio Kemandirian Daerah - Falaha Hasanatul Ummah; Meilani Purwanti (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this research is to shed light on the Bandung City Government's fiscal performance by analysing three key indicators: the Regional Independence Ratio, the Effectiveness Ratio, and the Efficiency Ratio. In this research, the three ratios were used to implement a qualitative methodology. According to the study's findings, the Bandung City Government has effective financial management and produces good financial outcomes generally. With an effectiveness ratio in the effective range for the years 2020–2023, the Bandung City Government should have no trouble reaching its (PAD) goal. It is necessary to reorganise the regional expenditure structure since, at the same time, the local government is deemed less efficient. The City of Bandung has moderate fiscal independence, according to the independence ratio, which indicates that the local government is beginning to have greater autonomy in managing the budget and development finance.